Effects of Obesity and Diabetes on Excitation-Contraction Coupling in Zucker Rat Cardiomyocytes - Sultan, Ahmed; Shmygol, Anatoliy; Qureshi, Muhammad Anwar; Howarth, Frank Christopher (Journal of Diabetes and Endocrine Practice, 2025)
Diabetes mellitus (DM) is a serious global health problem and obesity is a major risk factor for DM. Cardiovascular complications are a major cause of morbidity and mortality in diabetic patients and electromechanical dysfunction has been widely reported in the diabetic heart. The aim of this study was to investigate the effects of obesity and diabesity on ventricular myocyte shortening and Ca2+ signaling in Zucker fatty (ZF) and Zucker diabetic fatty (ZDF) rats, compared to Zucker lean (ZL) rats.Ventricular myocytes were isolated by enzymatic and mechanical dispersal. Myocyte shortening, L-type Ca2+ current, and intracellular Ca2+ dynamics were investigated with video imaging, whole cell patch clamp, and fluorescence photometry techniques, respectively.Time to peak (TPK) shortening was prolonged in ZDF (158.59 ± 3.05 ms) compared to ZF (130.33 ± 2.57 ms) and ZL (126.54 ± 3.09 ms) myocytes. The TPK Ca2+ transient was prolonged in ZF (67.26 ± 5.69 ms) compared to ZL (51.54 ± 2.32 ms) myocytes and the time to half (THALF) decay of the Ca2+ transient was prolonged in ZDF (155.35 ± 2.92 ms) compared to ZF (131.11 ± 3.26 ms) and ZL (129.17 ± 3.12 ms) myocytes. TPK and THALF decay of caffeine-evoked Ca2+ transients were prolonged in ZDF compared to ZF and ZL myocytes.Although the amplitude of shortening was generally well preserved in ZF and ZDF compared to ZL myocytes, the TPK shortening was prolonged in ZDF myocytes, which might partly be explained by defective uptake and release of sarcoplasmic reticulum Ca2+ in ventricular myocytes from the ZDF rat.
Keywords: ventricular myocytes; shortening; intracellular Ca2+; L-type Ca2+ current; Zucker fatty rat; Zucker diabetic fatty rat; Zucker lean rat